PEMEROLEHAN BAHASA ANAK USIA 3 BULAN — 2 TAHUN (Studi Kasus pada Muhammad Zaini) - M. Rafiek (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
This study aims to describe and explain the first syllable and words or phrases spoken by Muhammad Zaini from the age of 3 months to 2 years of age. This study uses a longitudinal approach with observing and recording techniques. The theory used in this study is the theory of the language acquisition from Steinberg, Nagata, and Aline and Crystal. This research is also supported by theory of first utterance phases from Steinberg, Nagata, and Aline and Piaget. The researcher manages to find the first syllable acquired by Muhammad Zaini, namely ma [mل]. This study also found other syllables Muhammad Zaini obtained after the first syllable, i.e bah ‘father’, a ‘eat’, tah ‘vomit’, dah ‘finished, da ‘three’, dai ‘cake’, ti ‘extinguished’, and pu ‘lights’. After acquiring syllables, then later Muhammad Zaini obtain such word abah ‘father’, totot ‘baby bottle’, inah ‘which means no or do not’, lalai ‘do not’, emma ‘mother’, mother, kaka ‘brother’, I, edah ‘already’, atit ‘ill’, eka or keka ‘open’, deda or kededa ‘no’, uah ‘fruit’, babah ‘sleep’, uka or kuka ‘open’, atu ‘ghost’, au ‘smell’, apu ‘light’ tutu ‘lid’, mau ‘want’, kukura ‘turtle’, ame ‘crowd’, auh ‘far’, dada ‘no’, manas ‘hot’, ngin ‘cold’ lalas ‘hard’, obiy ‘car’, babaluh ‘deep pool’, abis ‘end or finish’, aju ‘forward’, sawat ‘airplane’, and wak ‘fish’. In addition there are also phrases, namely abah...ku ‘my...father’, mama...ku ‘ my...mother’, kaka...ku ‘...my...brother’, sakit babarut ‘stomach ache’, ta api ‘train’, and mati puaw ‘die back or die again’.